2020
DOI: 10.2147/cia.s256599
|View full text |Cite
|
Sign up to set email alerts
|

<p>Barriers and Facilitators to Older Adults Participating in Fall-Prevention Strategies After Transitioning Home from Acute Hospitalization: A Scoping Review</p>

Abstract: Purpose: Approximately, 14% of older adults aged 65 years and over experience a fall within 1 month post-hospital discharge. Adequate self-management may minimize the impact of these falls; however, research is lacking on why some older adults engage in self-management to prevent falls while others do not. Methods: We conducted a scoping review to identify barriers and facilitators to older adults participating in fall-prevention strategies after transitioning home from acute hospitalization. Eligibility crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The contributors to adverse events among short-stay SNF residents identified herein were similar to those found for older adults participating in fall-prevention strategies after transitioning home from acute hospitalization. 30 The present study validates the importance of identifying individualized resident care plans during short SNF stays for rehabilitation. These intrinsic factors were inevitably related and thus contributed to singular adverse event incidents, such as falls and medication errors, and contributed additively and synergistically to other adverse events.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…The contributors to adverse events among short-stay SNF residents identified herein were similar to those found for older adults participating in fall-prevention strategies after transitioning home from acute hospitalization. 30 The present study validates the importance of identifying individualized resident care plans during short SNF stays for rehabilitation. These intrinsic factors were inevitably related and thus contributed to singular adverse event incidents, such as falls and medication errors, and contributed additively and synergistically to other adverse events.…”
supporting
confidence: 77%
“…22 Previous studies supported the importance of addressing communication and older adults' engagement in individualized care to improve their safety, prevent falls at home, enhance health quality, and promote self-care among community-dwelling older adults. 10,30,33,34…”
mentioning
confidence: 99%
“…A recent scoping review that used the COM-B framework as an analytical and descriptive guide identified a wide variation in barriers and enablers to older people participating in fall prevention activities after hospital discharge. A key barrier noted was self-denial of personal fall risk and a key enabler was follow-up with the older person post-discharge (Tzeng et al, 2020). A previous crosssectional study in the USA found that although over 90% of patients who were readmitted to hospital within 30 days of discharge understood their discharge plans, more than half reported experiencing difficulty in self-care, and about one-third of them reported a low anticipatory guidance for resolving these issues after discharge (Greysen et al, 2016).…”
Section: Barriersmentioning
confidence: 99%
“…The importance of incorporating community engagement in research on fall prevention has been highlighted in the literature [ 3 ]. Engaging patients and families in the fall prevention process during acute hospital stays is associated with a 15% reduction in falls and a 34% reduction in fall-related injuries [ 11 , 12 ].…”
Section: Approachmentioning
confidence: 99%
“…Patient-centered outcomes research can occur in diverse settings and include participants from across the care continuum (e.g., health care providers from primary care, secondary or tertiary settings). [ 1 ] One example is to identify the best way for health care providers to overcome obstacles to providing fall prevention education to community-dwelling older patients when they return home from acute hospitalization [ 3 ].…”
Section: Introductionmentioning
confidence: 99%